Fotoformas: a poética do processo interventor de Geraldo de barros na práxis fotográfica - Batista, Paulo Henrique Camargo (2006)
Through the visual poetics and photographic proposal – Fotoformas – initiate in the decade of 1940 by Geraldo de Barros (1923-1998), recognized as one of the accountable by the appearance of the modern photograph aesthetics in Brazil, this work attempts to demonstrate the possibility of disruption with the common praxis of the process of photographic images constitution. We based, theoretical and conceptually, our study, in the conceptions of Vilém Flusser and Arlindo Machado, from a conceptual perspective of intervention in the process of photographic images construction and of disruption with the programs of the semiotic devices (photographic machine), as a way the user not only depend on the options of choices disposed by machine program, without trying to understand or to interfere into its information coding process. We conclude that Geraldo de Barros is a clear example of conceptual and aesthetic disruption with the operation of photographic device programs, for interfering directly in the registration of the images (technical images) when producing them not repeating the coding process already programmed on the machine. We observed that in his photographic production, Geraldo de Barros acted in an inventive way and in the search of plural results in significance and experimentation, continually being ruled by his expressive freedom and avant-garde posture to reconcieve and reelaborate the semiotics function of the mediator apparatus and of the photographic technique, adding new elements to its productive system.